Comparative Pitching Biomechanics Among Adolescent Baseball Athletes: Are There Fundamental Differences Between Pitchers and Non-pitchers? - Garrett Bullock; Tessa C Hulburt; Gary Collins; Brian R Waterman; Kristen F Nicholson (International Journal of Sports Physical Therapy)
# Background